Oromandibular Dystonia: A Clinical Examination of 2,020 Cases - Scorr, Laura M.; Factor, Stewart A.; Parra, Sahyli Perez; Kaye, Rachel; Paniello, Randal C.; Norris, Scott A.; Perlmutter, Joel S.; Bäumer, Tobias; Usnich, Tatiana; Berman, Brian D.; Mailly, Marie; Roze, Emmanuel; et al. (Frontiers in Neurology, 2021)
Abstract: Objective: The goal of this study is to better characterize the phenotypic heterogeneity of oromandibular dystonia (OMD) for the purpose of facilitating early diagnosis. Methods: First, we provide a comprehensive summary of the literature encompassing 1,121 cases. Next, we describe the clinical features of 727 OMD subjects enrolled by the Dystonia Coalition (DC), an international multicenter cohort. Finally, we summarize clinical features and treatment outcomes from cross-sectional analysis of 172 OMD subjects from two expert centers. Results: In all cohorts, typical age at onset was in the 50s and 70% of cases were female. The Dystonia Coalition cohort revealed perioral musculature was involved most commonly (85%), followed by jaw (61%) and tongue (17%). OMD more commonly appeared as part of a segmental dystonia (43%), and less commonly focal (39%) or generalized (10%). OMD was found to be associated with impaired quality of life, independent of disease severity. On average, social anxiety (LSA score: 33±28) was more common than depression (BDI II score: 9.7±7.8). In the expert center cohorts, botulinum toxin injections improved symptom severity by more than 50% in approximately 80% of subjects, regardless of etiology. Conclusions: This comprehensive description of OMD cases has revealed novel insights into the most common OMD phenotypes, pattern of dystonia distribution, associated mood disturbances, and effect on QoL. We hope these findings will improve clinical recognition to aid in timely diagnosis and inform treatment strategies. Keywords: Dystonia, Jaw, Tongue, Treatment, Botulinum toxin